Anti-epidermal growth factor receptor (EGFR) monoclonal antibody combined with cisplatin and 5-fluorouracil in patients with metastatic nasopharyngeal carcinoma after radical radiotherapy: a multicentre, open-label, phase II clinical trial. (23rd January 2019) - Zhao, C; Miao, J; Shen, G; Li, J; Shi, M; Zhang, N; Hu, G; Chen, X; Hu, X; Wu, S; Chen, J; Shao, X; et al.
Abstract: Background: We conducted a single-arm phase II trial to evaluate the efficacy and adverse effects (AEs) of an anti-epidermal growth factor receptor monoclonal antibody, nimotuzumab, combined with cisplatin and 5-fluorouracil (PF) as first-line treatment in recurrent metastatic nasopharyngeal carcinoma after radical radiotherapy. Methods: Patients who met the eligibility criteria were recruited from ten institutions (ClinicalTrials.gov; NCT01616849). A Simon optimal two-stage design was used to calculate the sample size. All patients received weekly nimotuzumab (200 mg) added to cisplatin (100 mg/m 2 D1) and 5-fluorouracil (4 g/m 2 continuous infusion D1–4) every 3-weekly for a maximum of six cycles. Primary end point was objective response rate (ORR). Secondary end points included disease control rate (DCR), progression-free survival (PFS), overall survival (OS) and AEs. Results: A total of 35 patients were enrolled (13 in stage 1 and 22 in stage 2). Overall ORR and DCR were 71.4% (25/35) and 85.7% (30/35), respectively. Median PFS and OS were 7.0 (95% CI 5.8–8.2) months and 16.3 (95% CI 11.4–21.3) months, respectively. Unplanned exploratory analyses suggest that patients who received ≥2400 mg nimotuzumab and ≥4 cycles of PF had superior ORR, PFS and OS than those who did not (88.9% versus 12.5%, P < 0.001; 7.4 versus 2.7 months, P = 0.081; 17.0 versus 8.0 months, P = 0.202). Favourable subgroups included patients with lung metastasis [HROS 0.324 (95% CI 0.146–0.717), P = 0.008] and disease-free interval of >12 months [HROS 0.307 (95% CI 0.131–0.724), P = 0.004], but no difference was observed for metastatic burden. The only major grade 3/4 AE was leukopenia (62.9%). Conclusion: Combination nimotuzumab-PF chemotherapy demonstrates potential efficacy, and is well tolerated as first-line chemotherapy regimen in recurrent metastatic nasopharyngeal carcinoma.